If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 5x + -18 + -4x = -36 Reorder the terms: -18 + 5x + -4x = -36 Combine like terms: 5x + -4x = 1x -18 + 1x = -36 Solving -18 + 1x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 1x = -36 + 18 Combine like terms: -18 + 18 = 0 0 + 1x = -36 + 18 1x = -36 + 18 Combine like terms: -36 + 18 = -18 1x = -18 Divide each side by '1'. x = -18 Simplifying x = -18

| 8x-3.8=-8x-7.0 | | 9-6(4v-1)=v+15 | | 5(7x+8)=-100 | | 6x+7=31 | | x^4-15x^2-16=0 | | a-7=1 | | 0.5k(11-k)+(6-k+1)=0.5(k+1)(11-k+1) | | x=4-7 | | -104+10x=50+3x | | 0.5k(11-k)+(6-(k+1))=0.5(k+1)(11-k+1) | | -113-4x=55-12x | | 0.5k(11-k)+(6-k+1)=0.5(k+1)(11-(k+1)) | | 7(3x+2)=224 | | 5x-56=112+11x | | 0.5k(11-k)+(6-(k+1))=0.5(k+1)(11-(k+1)) | | 9x+2=4x-7 | | -3x-92=7x+138 | | 0+0=1 | | (x-8)(3x+1)=0 | | 48-8x=16 | | -8x-152=x+100 | | -109-2x=43-10x | | 4(x-2)+4=5x+4 | | y=x^2+4x-9 | | 64x^2=9 | | -42-2x=-6x+34 | | 3x-3y=8 | | 3x^4-24x^3+49x^2-8X+16=0 | | 2(x-5)-8=20 | | -5x-160=4x+47 | | -59-6x=95+x | | -99-6x=171+12x | | 3+4(p+2)=2p+3(p+4) | | -10+1-7x=17x+7 | | -7(5x+3)=-91 | | (8x+3)(8x-3)=0 | | -10x+1-7x=17x+7 | | 12x^2-11x=0 | | -12+4c=6c-(19+13) | | 3x^2+8x+5=1 | | 3t^2-1=6 | | x+283=681 | | 5x-1+90+2x=180 | | (x-6)(x+1)=-10 | | 5=6h+5h-25 | | 5(t+2)-2=6t-9 | | -(7y+1)-(-6y-3)=-6 | | -4(1x+10)=-68 | | 6+2n=3n-(6+5) | | (5x)(x+1)=0 | | r+4=-2 | | 5x-3=3x-49 | | 960=n*16 | | 7(a-3)=6(a-2) | | u^2-2u-2=0 | | 6x-5-3x=4 | | 10x-2+4.5x-5+5x-8=180 | | -6a+5=-2a+-3 | | -4x-6-3x=5 | | 9(p-2)=8(p-2) | | V=L*W*H | | 6x-129+4x=91 | | 3(2x+2)=9x+2-3x+4 | | 8(2x-1)-5x=25 | | 2t-4= |